Միջին հայերենյան փոխառությունների գործածությունը XIV դարի երկերում - Խաչատրյան, Վալենտին (ԳԱԱ ԼԻ հրատ․)
В статье рассматриваются заимствования из среднеармянского периода, зафиксированные в армянских произведениях XIV века. Данные слова были классифицированы и представлены по семантическим группам. The Use of Middle Armenian Borrowings in Works of the XIV Century.- The article examines borrowings from the Middle Armenian period recorded in Armenian works of the 14th century. These words were classified and presented by semantic groups.
Keywords: Բառագիտություն